2006
DOI: 10.1182/blood-2005-10-4244
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin overcomes the thrombosis defect associated with platelet GPVI/FcRγ deficiency

Abstract: Fibrillar collagens are among the most potent activators of platelets and play an important role in the initiation of thrombosis. The glycoprotein VI (GPVI)/FcR␥-chain complex is a central collagen receptor and inhibitors of GPVI produce a major defect in arterial thrombogenesis. In this study we have examined arterial thrombus formation in mice lacking the GPVI/ FcR␥-chain complex (FcR␥ ؊/؊ ). Using 3 distinct arterial thrombosis models involving deep vascular injury, we demonstrate that deficiency of GPVI/Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
127
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 39 publications
18
127
0
2
Order By: Relevance
“…This notion is supported by recent elegant studies indicating that in models that favor thrombin-driven thrombosis, the antithrombotic effect of GPVI deficiency is reduced or overcome. 41,42 This agrees with the observation that GPVI inhibition or loss has a relatively mild effect on normal hemostasis in humans and mice, 4,13-17 a process also known to be highly thrombin dependent. Thus, anti-GPVI treatment could be preferable to inhibitors of pathways that are crucial for thrombus formation, irrespective of the initial stimulus, and are also powerful antithrombotics (but by definition also bear a bleeding risk).…”
supporting
confidence: 80%
“…This notion is supported by recent elegant studies indicating that in models that favor thrombin-driven thrombosis, the antithrombotic effect of GPVI deficiency is reduced or overcome. 41,42 This agrees with the observation that GPVI inhibition or loss has a relatively mild effect on normal hemostasis in humans and mice, 4,13-17 a process also known to be highly thrombin dependent. Thus, anti-GPVI treatment could be preferable to inhibitors of pathways that are crucial for thrombus formation, irrespective of the initial stimulus, and are also powerful antithrombotics (but by definition also bear a bleeding risk).…”
supporting
confidence: 80%
“…Furthermore, inhibition of thrombin resulted in diminished platelet adhesion to collagen. Mangin et al (40) reported that thrombin was able to compensate for the effect of GPVI/FcR␥ deficiency in mouse platelets in in vivo models of thrombosis. The mechanism we describe, selective enhancement of the adhesive activity of the ␣ 2 ␤ 1 integrin via PAR4 activation, is the likely explanation for the observations of van der Meijden et al (39) and Mangin et al (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of GPVI, the absence of this platelet receptor does not create an inherent bleeding phenotype in vivo, and defects in thrombus formation or prolonged bleeding in vivo are dependent upon the genetic background at Mh. Thus, conclusions from previously established murine models of GPVI deficiency in animals with mixed backgrounds, whether induced by immune-mediated down-regulation 9,10 or targeted gene disruption of related molecules, such as FcR␥, 11,20 or even direct targeted disruption of Gp6 itself, 21 need to be reevaluated. Moreover, the indication of GPVI as a target for antithrombotic intervention must also be reconsidered, because its potential efficacy as well as side effects may be influenced by putative human equivalents of Mh genes.…”
Section: Discussionmentioning
confidence: 99%
“…GPVI is considered a major receptor that mediates collagendependent platelet function, an assertion that finds support in the complete lack of collagen-initiated platelet responses in vitro in mice that are genetically FcR␥ deficient, 9,20 that are temporarily GPVI-depleted by administration of JAQ1, 10 and that are Gp6 Ϫ/Ϫ . 8 All of the Gp6 Ϫ/Ϫ mice in our current study exhibit markedly deficient platelet responses in ex vivo perfusion studies on fibrillar type I collagen and a virtual absence of in vitro collagen-induced platelet aggregation, as expected.…”
Section: Discussionmentioning
confidence: 99%